(–)-Epicatechin and Anthocyanins Modulate GLP-1 Metabolism: Evidence from C57BL/6J Mice and GLUTag Cells. Issue 6 (10th March 2021) - Cremonini, Eleonora; Daveri, Elena; Mastaloudis, Angela; Oteiza, Patricia I
ABSTRACT: Background: Generated in intestinal L cells through cleavage of proglucagon (Gcg), glucagon-like peptide 1 (GLP-1) is secreted and rapidly inactivated by dipeptidyl peptidase IV (DPP-IV). GLP-1 regulates insulin secretion and overall glucose homeostasis. The capacity of dietary bioactives to increase GLP-1 circulating levels, and therefore increase insulin secretion and glucose metabolism, has gained significant interest of late. Objectives: We evaluated the effects of (–)-epicatechin (EC) and different anthocyanins (ACs) and AC metabolites on GLP-1 metabolism in mice and on GLUTag cells. Methods: We fed 6-week-old C57BL/6J male mice a control diet or a control diet supplemented with either 40 mg AC or 20 mg EC/kg body weight for 14 weeks (AC) or 15 weeks (EC). Intestinal mRNA levels of Gcg and Dpp-iv were measured. In vitro, GLUTag cells were incubated in the presence or absence of different ACs, the AC metabolite protocatechuic acid (PCA), and EC. GLP-1 secretion and the main pathways involved in its release were assessed. Results: Long-term supplementation with EC or AC increased mouse GLP-1 plasma concentrations (55% and 98%, respectively; P  < 0.05). In mice, 1 ) EC and AC increased Gcg mRNA levels in the ileum (91%) and colon (41%), respectively ( P  < 0.05); and 2 ) AC lowered ileum Dpp-iv mRNA levels (35%), while EC decreased plasma DPP-IV activity (15%; P  < 0.05). In GLUTag cells, 1 ) cyanidin, delphinidin, PCA, and EC increased GLP-1 secretion (53%, 33%, 53%, and 68%, respectively; P  < 0.05); and 2 ) cyanidin, delphinidin, EC, and PCA increased cyclin adenosine monophosphate levels (25–50%; P  < 0.05) and activated protein kinase A (PKA; 100%, 50%, 80%, and 86%, respectively; P  < 0.05). Conclusions: In mice, EC and ACs regulated different steps in GLP-1 regulation, leading to increased plasma GLP-1. Cyanidin, delphinidin, PCA, and EC promoted GLP-1 secretion from GLUTag cells by activating the PKA-dependent pathway. These findings support the beneficial actions of these flavonoids in sustaining intestinal and glucose homeostasis through the modulation of the GLP-1 metabolism.